Dileme kaznivega dejanja neupravičene izdaje poklicne skrivnosti - Šepec, Miha (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2017)
Disclosure of professional secrecy is incriminated in Article 142 of the Slovenian Penal Code (KZ-1). The offence protects the privacy of individuals in order to protect them from abuse when personal information and secrets are communicated to persons of certain professions (doctors, lawyers, priests, etc.). The issue is analyzed briefly; however, the context raises extremely complex dogmatic issues, particularly in the direction when unlawfulness of the crime shall be excluded, whether it is reasonable that such a complex offence is not prosecuted ex officio or upon request by the injured person, and the nature of relationship between the offence of disclosure of professional secrecy according to Article 142 and offences under Articles 280 (Failure to Inform Authorities of Preparations for Crime) and 281 (Failure to Provide Information of Crime or Perpetrator) of the Slovenian Penal Code. The aim of this paper is to highlight some legal dogmatic issues that have not yet been discussed in legal practice. On the other hand, the authors would also like to urge the legislature to amend the current criminal offence of disclosure of professional secrecy.
Keywords: criminal law; kazensko pravo; professional secrecy; kazniva dejanja; disclosure of secrecy; poklicne skrivnosti; the penal code; privacy; kazenskopravna analiza; kazenski zakoniki; criminal law analysis